Are there Gender-specific Preferences for Location Factors? A Grouped Conditional Logit-Model of Interregional Migration Flows in Germany - Lutz Schneider; Alexander Kubis (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
The article analyses the question whether women and men differ in their tastes for location factors. The question is answered by quantifying the impact of location characteristics on interregional migration flows across Germany. The analysis is based on a grouped conditional logit approach. We augment the framework by controlling for violation of the independence of irrelevant alternatives assumption and for overdispersion. As a result, we find no differences in terms of direction of impact. However, the regressions confirm gender differences in terms of intensity, particularly regarding regional wage levels and the availability of educational institutions. – – Die vorliegende Analyse untersucht die regionalen Determinanten geschlechtsspezifischer Binnenwanderungsflüsse und fragt, ob bestimmte Ausstattungsmerkmale eher von Frauen als von Männern geschätzt werden. Die Untersuchung basiert auf einem Grouped-Conditional-Logit-Ansatz, wobei die Probleme der Unabhängigkeit von irrelevanten Alternativen und der Überdispersion berücksichtigt werden. Im Ergebnis zeigt sich zunächst, dass bei Frauen und Männern dieselben Größen als Pulloder aber als PushFaktoren wirken. Geschlechtsspezifische Unterschiede werden indes hinsichtlich Stärke des Einflusses sichtbar, vor allem im Hinblick auf das regionale Lohnniveau und das Angebot an Bildungseinrichtungen.
urn:nbn:de:gbv:3:2-8714
Keywords: C25; J61; J16; R23; 330; Labour Mobility; Gender Economics; Regional Migration; Discrete Choice Model; Arbeitsmarktmobilität; Geschlechtsdifferenz; Binnenwanderung; Discrete-Choice-Modell; Regionale Arbeitsmobilität; Binnenwanderung; Geschlecht; Diskrete Entscheidung; Frauen; Deutschland